PENGARUH JUS DAUN SIRIH (Piper betle Linn) SEBAGAI BAHAN PRACURING TERHADAP KUALITAS DENDENG AYAM PETELUR SELAMA PENYIMPANAN - DAMAYANTI INDRIASTUTI, A. TENNY ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of the experiment was to know the effect ofjuice of betel leaf (Piper betle Linn.) on pre-curing process and its effect on chemical properties, peroxide value, total bacteria and sensory characteristics of processed chicken. Chicken meat was soaked into betel leaf juice (0, 5, 10 dan 15%), processed to become dendeng and stored at room temperature for 0 week, 2 weeks, 4 weeks, 6 weeks and 8 weeks. The variables measured included moisture, protein content, fat content, pH, peroxide value and total bacteria. The experimental design used was Completely Randomized Design (4 x 5)and followed by Tukey test.The sensory data were analyzed by using Kruskal-Wallis Hedonic test. The results showed that higher concentrations of Betel leaf juice significantly affected (P<0.05) moisture, protein content, fat content, peroxide value, totalbacteria and sensory characteristics of chicken dendeng that included color, aroma, taste and acceptability. Storage times up to eight weeks affected significantly (P<0.05) on pH, peroxide value and total bacteria. Interactions between the concentration of juice and storage times on peroxide value and total bacteria.The conclusion of this research was that the betel leaf juice could be applied up to concentration of 15%because it could suppress peroxide value, decrease total bacteria and extend storage times of the chicken dendeng. Sensory analysis showed that the best quality of the chicken dendeng was obtained at concentration of 10% with storage times of eight weeks.